2011
DOI: 10.1002/cjce.20445
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic granular treatment of 2,4‐dichlorophenol

Abstract: 2,4-Dichlorophenol (2,4-DCP) fed aerobic granules were cultivated in a sequencing batch reactor (SBR). Stable and compact granules were obtained in 60 days of SBR operation. Formed granules were compact and strong with closed packed channels. After granulation, effluent chemical oxygen demand and 2,4-DCP concentrations were 95 and 2.5 mg L −1 with corresponding removal efficiencies of 96% and 95% were achieved. Degradation profile shows a high initial degradation rate which decreases later. Degradation rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Several techniques such as physical, chemical, electrochemical and biological methods have been proposed for efficient wastewater treatment, most of them presenting some limitations such as poor capacity, generate waste products, incomplete mineralization or high operating cost (Gonzalez et al, 2010;Mondal et al, 2010). Nowadays aerobic granulation treatments are considered to be the most effective route (Khan et al, 2010;Wang et al, 2007). Aerobic granulation is a process of microbial self-immobilization, resulting into a cell-structured shape characterized by dense biomass (Khan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques such as physical, chemical, electrochemical and biological methods have been proposed for efficient wastewater treatment, most of them presenting some limitations such as poor capacity, generate waste products, incomplete mineralization or high operating cost (Gonzalez et al, 2010;Mondal et al, 2010). Nowadays aerobic granulation treatments are considered to be the most effective route (Khan et al, 2010;Wang et al, 2007). Aerobic granulation is a process of microbial self-immobilization, resulting into a cell-structured shape characterized by dense biomass (Khan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These particles served as the cores of granules and stimulate the granulation. FTIR, GC/MS showed that 2-CP biodegradation occurred via chlorocatechol and modified ortho-cleavage pathway Khan et al (2011a) 2,4,6-TCP degradation by aerobic granules in presence of glucose and acetate as co-substrates. Nitrate presence was the best option for phosphorus-rich effluents (3.04 mg P mg −1 N), while nitrite was more useful with the simultaneous nitrification-denitrification and phosphorus removal of nitrogen-rich influents (1.68 mg P mg −1 N) Coma et al (2010) Bioremediation of 2-CP by aerobic granules in SBR Aerobic granules were successfully cultivated for removing 2-CP with a COD removal efficiency of 94%.…”
Section: Role Of Denitrification On Aerobic Granular Sludge Formationmentioning
confidence: 98%
“…The knowledge of kinetics of aerobic biodegradation of toxic substances is a very important issue both for the prediction of their fate and the design of wastewater treatment plants (Khan et al, 2011a). The kinetic investigations were carried out to study the time required for the attainment of equilibrium during the biodegradation of toxic compounds.…”
Section: Kinetics and Thermodynamicsmentioning
confidence: 99%
See 2 more Smart Citations